The evaluation of the appropriateness of railway subgrade restoration With an unconventional material - Gombitová, Janka (Communications - Scientific letters of the University of Zilina, 1999)
This paper deals with the results achieved during the testing of a new geosynthetic reinforcing material - GEOWEB, which was used for the restoration of railway subgrade. Conventionally used materials are no longer sufficient for reconstruction works within the modernisation of railway tracks and stations.